Basin characteristics, river morphology, and process in the Chure-Terai landscape: A case study of the Bakraha river, East Nepal - Ghimire, Moti Lal (Geographical Journal of Nepal, 2020)
The study aims to illustrate the basin characteristics, river morphology and river processes in the Chure- terai Landscape. The basin and morphological variables used in the study were derived from the satellite imageries available on Google earth, digital elevation models, and relevant maps. The cross-section survey and hydrometric data, incorporated in the study were obtained from the secondary sources, reports, and documents. The Bakraha River basin is underlain by the rocks of the Siwalik group in the south. The rocks are highly deformed and fractured and have the steep and variable slope and are subject to strong seismic shaking. The network of drainage is dense, with the predominance of colluvial streams that receive sediments from slope failure and erosion. The steep profile of the river demonstrates the ability to transport a huge sediment load during a high flood. The climatic regime and daily annual extreme rainfall between 100-300mm can initiate shallow landslides to large and deep-seated landslides. Landslides very large, small to shallow types are quite numerous, which indicates terrain highly susceptible to slope failure and erosion. The forest cover is above 84% but largely has been degraded and interspersed by agricultural patches and settlements with population dependent on agriculture and livestock. The lower catchment has dominant agricultural land use. The role of riparian vegetation for bank protection and flood control is limited. In the hilly areas, the river reaches are mainly sinuous to straight controlled by bedrock and in Terai, the reaches are straight, wandering to meandering towards the south. River slope is very steep, up to 15.2% in hills and mild in the meandering reaches in Terai decreasing to 0.1%. In the straight reaches, sediments are mainly boulders, gravels, bedrocks and sands in the hill, while in meandering reaches in Terai, sediments are sand and silt. The discharge varies 200-734 cusec from upstream (close to outlet) to downstream, (16.5 km away). The estimated sediment load transport during extreme flood events highly varies. Potential sediment load decreases from straight to meandering reaches, with some fluctuations in certain locations, owing to change in local morphological conditions. Bank erosion, bend scour, confluence scour, and protrusion scours, and avulsions are the river processes, which provide a source of sediments to the river. Change in planform and cross-section view of the river morphology indicate the river is unstable and dynamic due to the frequent shifts between accretion to erosion processes.